Primary Angioplasty for the Treatment of Acute ST Elevated Myocardial Infarction: Single Centre Experience - Begum, F; Khan, KN; Momenuzzaman, NAM; Sohail, KM; Haque, SMZ; Shafique, AM; Mallick, SK; Rahman, R; Amin, MM; Rahman, M; et al. (Cardiovascular Journal, 2011)
Background: Worldwide primary angioplasty is a recommended strategy of reperfusion in patient with acute myocardial infarction as because it ensures reperfusion of the infarct-related vessels more than 90% where as, with thrombolytics it is only 60-70%. Methods: It is a retrospective observational study includes all patients treated with primary angioplasty at United Hospital from Between March 2007 to August 2010. Total 237 consecutive patients with acute myocardial infarction were treated with primary angioplasty were included. Those presented beyond 12 hours of onset of chest pain, in cardiogenic shock, resuscitate and intubated before the procedural were excluded from the study. Results: Majority (76%) of the patient were male, age was minimum 28 years and maximum 80 years, 41.5% were diabetics, 58.4% were hypertensive, 43.5 %were dyslipidaemic, 17% were smoker, 29.3% with positive family history. Fifty seven percent patients presented with anterior MI, 42 % with inferior MI and 1 % with lateral MI. Left anterior descending (LAD) is the most common vessel involved (S7%), followed by Right coronary artery (RCA) 31 %, Left circumflex artery (LCD 8 %, Ramus 1.3 % and Graft vessel 2.7%. Our door to balloon time was minimum 23 min, maximum 184 min. We used drug eluting stents for most of the patients , GP IIbIIIa receptor Mockers used in 50% cases and thrombus suction device were used when indicated. We faced complications like arrhythmias in 24% hypotension in18 %, no flow or slow flow in 45%, cardiac arrest in 3% and coronary perforation in 1. %. Our overall survival was 97.9 %. Conclusion: Primary angioplasty is a emerging area in the context 149-154of our country . Many of the new centers start this novel strategy which helps to save many lives. Primary angioplasty is feasible and safe method of reperfusion in patient with acute myocardial infarction in our center. Keywords: Primary angioplasty; ST elevation MI DOI: http://dx.doi.org/10.3329/cardio.v3i2.9184 Cardiovasc. J. 2011; 3(2): 149-154